Peran Strategis Masyarakat Sadar Wisata Dalam Meningkatkan Ekonomi Kreatif Pariwisata (Studi Empiris: Desa Ujung Pandaran Kecamatan Teluk Sampit Kabupaten Kotawaringin Timur) - Maria Christina Yuli Pratiwi (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2020)
Community empowerment through awareness of the importance of protecting and maintaining natural resources to improve the rural economy is one of the strategic way to realize the East Kotawaringin Regency especially Ujung Pandaran Village as a tourist destination. Using quantitative descriptive methods with data collection through interviews, questionnaires, observation, and documentation. This study aims to determine the role of the Ujung Pandaran Village community in supporting and developing tourism activities, also to identify the tourism potency and creative industries in Ujung Pandaran Village. The result of study finds the role of Ujung Pandaran Village community both individually and in groups (Pokdarwis Garda Pesisir) is active, although not yet fully. Participation of local community is classified as citizen power participation, an ideal community participation which the community has the discretion in participating of determining the future of their village and be able to control the performance of regional government. The tourism potency of Ujung Pandaran Village is very large to be developed. Ujung Pandaran Village’s tourism objects are quite complete, from natural tourism, education, religion and culture. Ujung Pandaran Village is famous with fishery products and the number of UMKM in this village is quite numerous, such as crab and small crab processing, making salted fish, shrimp paste and cracker from fish egg, also shellfish handicraft. The policy references are recommended for the Regional Government in developing Ujung Pandaran Village based on the creative economy as follows: involve creative industry businesses in managing and implementing tourism activities; also strengthening institutional through capacity building for groups who concern with tourism. In addition, to promote tourism in Ujung Pandaran Village, the Regional Government develop cooperation with business society (travel and hotels) and local communities, improve promotion through social media, also the most important are repair and fix the facilities and infrastructure of supporting tourism.